Produkty niskoenergetyczne - nowy segment rynku żywnościowego - Adamowicz, Mieczysław (Low Energy Products - A New Segment of Food Market, 2005)
Along with the better supply of food and with increasing level of life, the new food preferences and the new food segments appear. One of such new segments is the low energy "light" food. The aim of the paper is to define these types of food and analyze the factors of increasing demand for it. Legal aspects of "light" food and methods of decreasing the energy contents are presented. The scale of low energy food products in the market activity of ANGO firm on Polish food market as well as consumer attitudes to "light" food are analysed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 17-24